3,5,3′-Triiodothyronine–Loaded Liposomes Inhibit Hepatocarcinogenesis Via Inflammation-Associated Macrophages - Sun, Gangqi; Hou, Xiaojuan; Zhang, Luyao; Zhang, Hengyan; Shao, Changchun; Li, Fengwei; Zong, Chen; Li, Rong; Shi, Junxia; Yang, Xue; Zhang, Li (Frontiers in Oncology, 2022)
Background Hepatocellular carcinoma (HCC) is inflammation-related cancer. Persistent inflammatory injury of the liver is an important factor mediating the occurrence and development of liver cancer. Hepatic macrophages play an important role in the inflammatory microenvironment, which mediates tumor immune escape, tumor growth, and metastasis. Previous studies have suggested that L-3,5,3-triiodothyronine (T3) can regulate inflammation; however, its use is associated with serious cardiac side effects, and its role in hepatocarcinogenesis remains unclear. In this study, we aimed to develop an effective T3 delivery system with reduced cardiac toxicity and to explore its effects on HCC occurrence. Methods T3 liposomes (T3-lipo) were prepared using the thin-film hydration method, and their characteristics, including particle size, polydispersity index, zeta potential, encapsulation efficiency, drug loading, drug release, and stability, were evaluated in vitro. We assessed the effect of T3-lipo on hepatocarcinogenesis in diethylnitrosamine (DEN)–induced primary HCC in rats and examined the biodistribution of T3 and T3-lipo by high-performance liquid chromatography–mass spectrometry. Furthermore, we explored the potential molecular mechanism of T3-lipo in hepatocarcinogenesis by immunohistochemistry and immunofluorescence analyses, Bio-Plex assays, real-time polymerase chain reaction analysis, and Western blotting assays. Results Compared with T3, T3-lipo had an enhanced inhibitory effect on hepatocarcinogenesis and reduced cardiac side effects in DEN-induced primary HCC in rats. Mechanistically, T3-lipo were absorbed by hepatic macrophages and regulated the secretion of inflammatory cytokines in macrophages by inhibiting inflammatory signaling pathways. Conclusions T3-lipo may suppress hepatocarcinogenesis by regulating the inflammatory microenvironment in the liver and reduce the cardiac side effects meanwhile.